2013
DOI: 10.1088/0268-1242/28/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

Development of ZnTe layers using an electrochemical technique for applications in thin-film solar cells

Abstract: Zinc telluride layers were grown by an electrochemical technique using acidic and aqueous solutions containing ZnCl 2 and TeO 2 . The layers were deposited on glass/fluorine-doped tin oxide substrates using a two-electrode system. The deposited ZnTe layers were characterized using x-ray diffraction, x-ray fluorescence, Raman spectroscopy, optical absorption, photoelectrochemical cell measurements, scanning electron microscopy and 3D-atomic force microscopy (3D-AFM) for the structural, optical, electrical and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The n-type electrical conductivity was achieved at higher cathodic potential due to Zn-richness. Fauzi et al [25] reported only p-type ZnTe even at higher cathodic potentials. This can be due to presence of higher concentrations of Te in the electrolyte.…”
Section: Analysis Of Electrical Propertiesmentioning
confidence: 98%
See 4 more Smart Citations
“…The n-type electrical conductivity was achieved at higher cathodic potential due to Zn-richness. Fauzi et al [25] reported only p-type ZnTe even at higher cathodic potentials. This can be due to presence of higher concentrations of Te in the electrolyte.…”
Section: Analysis Of Electrical Propertiesmentioning
confidence: 98%
“…It has been shown that Te being a nobler element deposits first [24,25] [27]. Since Te shows a more positive redox potential than Zn, it is therefore expected to deposit first.…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
See 3 more Smart Citations